Buprenorphine and Naloxone Compared With Methadone Treatment in Pregnancy. Issue 2 (February 2015) - Wiegand, Samantha L.; Stringer, Elizabeth M.; Stuebe, Alison M.; Jones, Hendree; Seashore, Carl; Thorp, John
Abstract : OBJECTIVE: To compare neonatal abstinence syndrome prevalence and characteristics among neonates born to women prescribed buprenorphine and naloxone compared with methadone during pregnancy. METHODS: Retrospective cohort analysis of mother–neonate dyads treated with either buprenorphine and naloxone or methadone during pregnancy. Primary neonatal outcomes included diagnosis of neonatal abstinence syndrome, neonatal abstinence syndrome peak scores, total amount of morphine used to treat neonatal abstinence syndrome (mg), and duration of treatment for neonatal abstinence syndrome (days). Secondary outcomes included head circumference, birth weight, length, preterm birth, neonatal intensive care unit admission, Apgar scores, and overall length of hospitalization. RESULTS: From January 1, 2011, to November 30, 2013, we identified 62 mother–neonate dyads, 31 treated with methadone and 31 treated with buprenorphine and naloxone. Sixteen neonates (51.6%) in the methadone group were diagnosed with neonatal abstinence syndrome compared with eight (25.1%) in the buprenorphine and naloxone group (adjusted odds ratio 2.55, 95% confidence interval [CI] 1.31–4.98, P =.01). The buprenorphine and naloxone-exposed neonates had lower peak neonatal abstinence syndrome scores (9.0±4.4 compared with 10.7±3.7, multivariate-adjusted mean difference=−2.77, 95% CI −4.99 to −0.56, P =.02) and shorter overall hospitalization (5.6±5.0 compared with 9.8±7.4 days, multivariate-adjusted mean difference=−3.90, 95% CI, −7.13 to −0.67, P =.02). We found no other differences in primary or secondary outcomes. CONCLUSION: In a cohort of pregnant patients treated with either methadone or buprenorphine and naloxone in pregnancy, newborns exposed to maternal buprenorphine and naloxone had less frequent neonatal abstinence syndrome. Additionally, neonates exposed to buprenorphine and naloxone had shorter overall hospitalization lengths. LEVEL OF EVIDENCE: II Abstract : Compared with methadone, maternal buprenorphine and naloxone treatment is associated with less frequent neonatal abstinence syndrome as well as shorter neonatal hospitalization.